2020
DOI: 10.1186/s13071-020-04418-2
|View full text |Cite
|
Sign up to set email alerts
|

External female genitalia of Triatoma jatai, Triatoma costalimai and Triatoma williami (Hemiptera: Reduviidae: Triatominae)

Abstract: Background Taxonomic identification of triatomines is generally performed based on aspects of their external morphology. However, the use of a multidisciplinary approach, considering morphological aspects of the external genitalia, morphometry, genetics, and phylogeography has been suggested, especially for similar and/or cryptic species. The rupestral species Triatoma jatai Gonçalves et al., 2013, Triatoma costalimai Verano & Galvão, 1959 and Triatoma williami Galvão et al., 1965, which are morphologicall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
(21 reference statements)
2
8
0
Order By: Relevance
“…In contrast, the low genetic divergence, lack of morphological diagnostic characters, and low morphometric distinction observed between T. guazu and T. williami corroborate previous studies which stated that they are very similar taxa [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Additionally, the variation in the spots pattern in the connexivum is compatible with phenotypic variations between populations of the same species, possibly a consequence of different ecological characteristics, not standing as a feature to consider them as a separate species [ 14 , 39 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In contrast, the low genetic divergence, lack of morphological diagnostic characters, and low morphometric distinction observed between T. guazu and T. williami corroborate previous studies which stated that they are very similar taxa [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Additionally, the variation in the spots pattern in the connexivum is compatible with phenotypic variations between populations of the same species, possibly a consequence of different ecological characteristics, not standing as a feature to consider them as a separate species [ 14 , 39 ].…”
Section: Discussionsupporting
confidence: 88%
“…Noireau et al [ 15 ] observed a great similarity between sympatric specimens of T. williami and T. guazu , collected in the male type locality of the latter species, when analyzing 18 isoenzyme loci and four measurements of each, the head and thorax structures through traditional morphometry. In regard to the genitalia of the species studied here, Lent et al [ 14 ] described the male genitalia of T. guazu and Teves et al [ 16 ] described the female genitalia of T. williami . The former authors illustrated their description with drawings, while the latter with Scanning Electron Microscopy images.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of T. williami was conducted based on external morphological characteristics. In such analyses, the importance of these structures in the identification of specimens was confirmed, as previously discussed by Teves et al [ 37 ].…”
Section: Discussionsupporting
confidence: 64%
“…2A-E). Such analyses con rmed the importance of these structures, as previously discussed by Teves et al (2020). Based on this information, the activities of the ChD surveillance team are triggered.…”
Section: Introductionmentioning
confidence: 53%